Institutional Design for Conflict Fesolution: An Examination of Institutional Designs for Waste Facility Siting Conflict - Kim, Dong Young (INTERNATIONAL REVIEW OF PUBLIC ADMINISTRATION, 2012)
Merely incorporating public participation and multiparty negotiation into a regulatory regime as new governance does not always translate to success in resolving public conflicts. In this article, I intend to discuss the role of institutional design as an explanatory factor of the success and failure of new governance institutions to cope with public conflict, by comparing three institutional arrangements to resolve waste facility siting controversies in the United States and South Korea. I argue that a certain regulatory recipe with flawed institutional design, regardless of its good intentions and rationales, might not be a solution to public conflict but rather part of the problem, and even exacerbate the problem. Flawed design is related to the tendency to control and formalize participatory negotiation, which dissipates perceived fairness, trust, and creativity among actors. Therefore, designers of new governance institutions should find ways to induce enforced self-regulation. © 2012 Taylor & Francis Group, LLC. All rights reserved.
Keywords: conflict resolution, institutional design, facility siting